Anticoagulant activity of a sulfated galactan: Serpin-independent effect and specific interaction with factor Xa - Glauser, Bianca F.; Rezende, Ricardo M.; Melo, Fabio R.; Pereira, Mariana S.; Francischetti, Ivo M. B.; Monteiro, Robson Q.; Rezaie, Alireza R.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2009)
An algal sulfated galactan has high anticoagulant and antithrombotic activities. Its serpin-dependent anticoagulant action is due to promoting thrombin and factor (F)Xa inhibition by antithrombin and heparin cofactor II. Here, we evaluated the anticoagulant effect of the algal sulfated galactan using serpin-free plasma. In contrast to heparin, the sulfated galactan is still able to prolong coagulation time and delay thrombin and FXa generation in serpin-free plasma. We further investigated this effect using purified blood coagulation proteins, discovering that sulfated galactan inhibits the intrinsic tenase and prothrombinase complexes, which are critical for FXa and thrombin generation, respectively. We also investigated the mechanism by which sulfated galactan promotes FXa inhibition by antithrombin using specific recombinant mutants of the protease. We show that sulfated galactan interacts with the heparin-binding exosite of FXa and Arg-236 and Lys-240 of this site are critical residues for this interaction, as observed for heparin. Thus, sulfated galactan and heparin have similar high-affinity and specificity for interaction with FXa, though they have differences in their chemical structures. Similar to heparin, the ability of sulfated galactan to potentiate FXa inhibition by antithrombin is calcium-dependent. However, in contrast to heparin, this effect is not entirely dependent on the conformation of the γ-carboxyglutamic acid-rich domain of the protease. In conclusion, sulfated galactan and heparin have some similar effects on blood coagulation, but also differ significantly at the molecular level. This sulfated galactan opens new perspective for the development of antithrombotic drugs.
Keywords: Antithrombotic drug; heparin; heparin-binding exosite; prothrombinase complex; sulfated galactan; tenase complex